City Leadership in Para-Diplomacy: The Case of Jakarta’s International Engagement in Addressing COVID-19 Pandemic - Luerdi, Luerdi (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
The outbreak of the COVID-19 pandemic impacted the world communities, including the interactions among governments. While some governments chose to conflict with others or overlooked the pandemic, the rest attempted to collaborate in addressing the new global threat. Cities in many countries were the most suffering regions due to the enormous virus-confirmed cases, deaths, and economic declines, intertwining with other urban issues. As the largest city in Southeast Asia and Indonesia, Jakarta could not avoid this unprecedented crisis. However, apart from the efforts to tackle the crisis at home, the city showed its international engagement in addressing the issue together with other world cities as its para-diplomacy. This article aimed to answer the driving factors that encouraged the city for such engagement. It employed the qualitative method with descriptive analysis and the city leadership theory proposed by Rapoport, Acuto and Grcheva. The article found that Jakarta’s international engagement in addressing the pandemic as the city leadership action was driven by the role of city leader, decentralization and global city networking, and the regional COVID-19 policies and internet representing three elements in the theory: actor, structures, and tools. It argues that cities within the global city networking have demonstrated their stronger role during the pandemic, providing opportunities for nation branding by regional initiatives in handling the pandemic in addition to state foreign policy. This study, then, contributes to the studies the city leadership in responding to global issues that merit attention among scholars.